Five-Year Retrospective Review of Acute Generalized Exanthematous Pustulosis - Chitprapassorn Thienvibul; Vasanop Vachiramon; Kumutnart Chanprapaph (Dermatology Research and Practice)
Background. Acute generalized exanthematous pustulosis (AGEP) is an acute pustular eruption characterized by widespread nonfollicular sterile pustules. The aim of this study is to characterize the etiology, clinical features, laboratory findings, management, and outcome of patients with AGEP in Asians. Patient/Methods. A retrospective analysis was performed on patient who presented with AGEP between August 2008 and November 2012 in a tertiary center in Thailand. Results. Nineteen patients with AGEP were included. AGEP was generally distributed in seventeen patients (89.5%) and localized in two (10.5%). Fever and neutrophilia occurred in 52.6% and 68.4%, respectively. Hepatitis was found up to 26.3%. The most common etiology was drugs (94.7%), comprising of antibiotics (73.6%), proton pump inhibitors (10.5%), nonsteroidal anti-inflammatory drugs (5.3%), and herbal medicine (5.3%). Beta-lactams were the most common causal drug, particularly carbapenems and cephalosporins. This is the first report of Andrographis paniculata as an offending agent for AGEP. We found no differences between various treatment regimens (topical corticosteroid, systemic corticosteroid, and supportive treatment) regarding the time from drug cessation to pustules resolution (P=0.171). Conclusions. We have highlighted the presentation of AGEP among Asians. We found high association with systemic drugs. Carbapenems were one of the leading culprit drugs. Finally, a localized variant was observed.